Big Data y Turismo Deportivo: Estado de la cuestión y nuevas aplicaciones - González Gómez, Sara; Rubio Gil, Ángeles (Eracle. Journal of Sport and Social Sciences, 2019)
The growing interest in sporting events, such as football, motorcycling, sailing, golf, basketball, etc., make every host population a destination, with the characteristics of the tourist product such as, for example, spatial and temporal concentration. In this environment, it is essential to improve the experience of visitors and tourists, which can be achieved through the large amount of data they provide properly analyzed, such as social networks, mobile devices, websites, sports applications, etc. creating value for the host society. The opportunity that Big Data represents for the development of sports tourism and its host destinations will be analyzed, and the literature on sports tourism will be exhaustively and systematically analyzed from the Big Data perspective, from the analysis of the tertiary sources Scopus and Web of Science.